1986
DOI: 10.7326/0003-4819-105-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Renal Function in Kidney Donors: A Comparison of Donors and Their Siblings

Abstract: To assess the effects of unilateral nephrectomy, we evaluated renal function and hypertension in kidney donors who had had nephrectomies 10 years ago or more and siblings who had not had nephrectomies. No statistically significant difference was found between the prevalence of hypertension in donors and siblings. Serum creatinine concentrations were 20% higher in donors and creatinine clearances, 20% lower than corresponding values in siblings. Twenty-four-hour urinary protein excretion increased in all donors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(88 citation statements)
references
References 19 publications
7
80
1
Order By: Relevance
“…The (10,11,13,19,25). The sum of the results of these five studies can be interpreted as showing that there is likely an increase in hypertension and proteinuria in male donors and, not unexpected, a loss of renal function of at least 20% in both genders.…”
Section: Comparisons and Controlsmentioning
confidence: 89%
See 2 more Smart Citations
“…The (10,11,13,19,25). The sum of the results of these five studies can be interpreted as showing that there is likely an increase in hypertension and proteinuria in male donors and, not unexpected, a loss of renal function of at least 20% in both genders.…”
Section: Comparisons and Controlsmentioning
confidence: 89%
“…Furthermore, because of tubular secretion of creatinine, both serum creatinine and creatinine clearance will overestimate GFR to a greater degree as renal function declines. This may lead to underestimation of decreases in renal function and the degree of renal dysfunction after donation in studies that rely on these measurements, as the majority do (11,12,(17)(18)(19)(20)23,25,40,45,47). This is demonstrated in a study by Watnick et al (24), in which postdonation creatinine clearance was only modestly decreased at 85 ml/min per 1.73 m 2 , whereas inulin clearance was 44% lower at 66 ml/min per 1.73 m 2 .…”
Section: Limitations In Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…After 18, 24, or 48 h (n ϭ 5-18/group), the right kidney (i.e., remnant kidney) was removed and processed using the same procedures as the left kidney (control kidney). Kidney growth was based on wet weight because we have previously found that the increase in kidney dry weight induced by UNX is proportional to wet weight and total protein (27).…”
Section: Unxmentioning
confidence: 99%
“…5,6 Some researchers have found an increase in BP after kidney donation, 7,8 and studies comparing donors with siblings or potential kidney donors have shown conflicting results for the impact of donation on BP, renal function, and proteinuria. 7,[9][10][11][12] It is complicated to dissociate the effects of the aging process from the influence of UNX, because both renal function and BP are influenced by age. Thus, in studies of ageand sex-matched populations, some 9,11,12 but not all 7 authors found differences in BP between kidney donors and the general population.…”
mentioning
confidence: 99%